Innovative Approaches in Arabic Language Learning: A Conceptual Study of PBL, PJBL, and Differentiated Learning Models - basarata, Nurhanifa; Daud, Devika Rahayu; Hasan, Adtman A. (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2025)
The purpose of this study is to identify how the three approaches can strengthen student engagement, deepen conceptual understanding, and develop communicative, creative, and collaborative Arabic language competencies. This research employs a descriptive qualitative method with a library research approach. Data were collected through a systematic review of various literature sources, scientific journals, and relevant studies from the past five years discussing the application of PBL, PJBL, and differentiated learning in the context of Arabic language education. The findings indicate that the integration of these three models can create a more participatory, contextual, and adaptive learning environment that meets students’ diverse needs. The project-based approach enhances productive skills (speaking and writing), while differentiated learning provides flexibility in accommodating different learning styles and proficiency levels. Therefore, the combination of PBL, PJBL, and differentiated learning is recommended as an effective pedagogical strategy to improve Arabic language competence and learning motivation in the modern educational era.